Butyrate interacts with benzo[a]pyrene to alter expression and activities of xenobiotic metabolizing enzymes involved in metabolism of carcinogens within colon epithelial cell models - Zapletal, Ondřej; Procházková, Jiřina; Dubec, Vít; Hofmanová, Jiřina; Kozubík, Alois; Vondráček, Jan (Toxicology, 2019)
Butyrate helps to maintain colon homeostasis and exhibits chemopreventive effects in colon epithelium. We examined the interactive effects of butyrate and benzo[a]pyrene (BaP), dietary carcinogen, in regulation of expression of a panel of phase I and II xenobiotic metabolizing enzymes (XMEs) in human colon cells. In human colon carcinoma HCT-116 and HT-29 cell lines, butyrate alone increased mRNA levels of some enzymes, such as N-acetyltransferases (in particular NAT2). In combination with BaP, butyrate potentiated induction of cytochrome P450 family 1 enzymes (CYP1A1), aldo-keto reductases (AKR1C1) or UDP-glucuronosyltransferases (UGT1A1). There were some notable differences between cell lines, as butyrate potentiated induction of NAD(P)H:quinone oxidoreductase 1 (NQO1) and UGT1A4 only in HCT-116 cells, and it even repressed AKR1C3 induction in HT-29 cells. Butyrate also promoted induction of CYP1, NQO1, NAT2, UGT1A1 or UGT1A4 in human colon Caco-2 cells, in a differentiation-dependent manner. Differentiated Caco-2 cells exhibited a higher inducibility of selected XME genes than undifferentiated cells. Butyrate increased induction of enzymatic activities of NATs, NQO1 and UGTs by BaP in HCT-116 and HT29 cells, whereas in differentiated Caco-2 cells it helped to increase only enzymatic activity of NQO1 and UGTs. Together, the present data suggest that butyrate may modulate expression/activities of several enzymes involved in metabolism of carcinogens in colon. In some cases (NAT2, UGT1 A1), this was linked to inhibition of histone deacetylases (HDAC), as confirmed by using HDAC inhibitor trichostatin A. These results may have implications for our understanding of the role of butyrate in regulation of XMEs and carcinogen metabolism in colon.
Keywords: kolon; Humans; Transferases; Polycyclic aromatic hydrocarbons; Colon epithelium; Butyrate; N-acetyltransferases; UDP-glucuronosyltransferases; epitelové buňky; Colon; lidé; Xenobiotics; buněčné linie; transferasy; oxidoreduktasy; Epithelial Cells; Cell Line; Butyrates; butyráty; Carcinogens; Benzo(a)pyrene; xenobiotika; karcinogeny; NAD(P)H:quinone oxidoreductase 1; Oxidoreductases; benzopyren